Neophytou Maro - (:unkn) unknown (My University, 2026)
Maro Neophytou – Yiokari is an Assistant Professor of English at the Language Centre of the Cyprus University of Technology. She holds a Degree in English Literature from the University of Athens (1975), a Diploma in Teaching English as a Foreign Language from the Institute of Education – London University (1981) and an M.A. in Applied Linguistics from the University of Essex. She has many years of experience in the teaching of English at Private Tertiary Education Colleges in Cyprus and the Higher Technical Institute where she worked as a Lecturer and Senior Lecturer. She specialised in the teaching of English for Specific Academic Purposes and her research interest concentrates primarily on this area as well as the area of testing. She has attended a number of conferences and seminars as well as workshops both in Cyprus and abroad related to the Common European Framework of Reference for Language (CEFR). She is a member of the Cyprus University of Technology Council and member of other committees of the Language Centre and the University.